Implementation of Rescheduling in Problematic Working Capital Financing According to DSN-MUI Fatwa No. 48/DSN-MUI/2005 at Bank Bsi Medan (Case Study: Bank BSI Jalan Setia Budi, Medan) - Ahmad Parlindungan Pasaribu; Ahmad Zuhri Rangkuti (SEAN Institute, 2025)
Study This done with objective For analyze Implementation of the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) No. 48/DSN-MUI/2005 concerning restructuring working capital financing problematic in form reschedule at Bank Syariah Indonesia (BSI) Medan Branch Office, Jalan Setia Budi. DSN-MUI Fatwa No. 48 of 2005 give guide for Islamic Financial Institutions (LKS) in overcome customers who experience difficulty payment with principle justice in accordance with Islamic teachings. Research This use approach qualitative with method studies case. Data obtained through the interview process with bank parties, and observations field. Research results show that Bank BSI Medan has implement the fatwa through procedure reschedule which includes review repeat term time and quantity installment financing with consider ability financial customers. Although in a way general implementation walk in accordance with sharia provisions, there are a number of constraint like delay response Customers. Research This recommend strengthening education to Customer related restructuring financing sharia based.